ECONOMIC DEVELOPMENT VS. ENVIRONMENTAL DEGRADATION: AN ENVIRONMENTAL KUZNETS CURVE (EKC) ANALYSIS ON CHINA - Srisueb, Sutiporn (2013)
China is one of the fastest growing economies in the world. It is very interesting to study what price it has paid to obtain this position. This dissertation is made to study the relationship between economic development and environmental degradation in China, whether the Environmental Kuznets Curve (EKC) characteristic is existed in Chinese economy. CO2 and PM10 are selected as environmental indicators while GDP indicates economic development. Regression analysis and t-test are conducted. The results show that EKC characteristic exist in Chinese economy and it is on declining stage, indicating China’s environment is in its recovering stage and getting better.